2021
DOI: 10.3389/fmed.2021.780611
|View full text |Cite
|
Sign up to set email alerts
|

Is the Infection of the SARS-CoV-2 Delta Variant Associated With the Outcomes of COVID-19 Patients?

Abstract: Background: Severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) Delta variant (B.1.617.2) has been responsible for the current increase in Coronavirus disease 2019 (COVID-19) infectivity rate worldwide. We compared the impact of the Delta variant and non-Delta variant on the COVID-19 outcomes in patients from Yogyakarta and Central Java provinces, Indonesia.Methods: In this cross-sectional study, we ascertained 161 patients, 69 with the Delta variant and 92 with the non-Delta variant. The Illumina MiS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
2
20
0
Order By: Relevance
“…Previous studies showed that older age and comorbidities are significant prognostic factors for hospitalization and mortality [13-15,33,34]. Our study further provides evidence that older age, diabetes, and cardiovascular diseases as strong prognostic factors for the outcomes of COVID-19 patients.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Previous studies showed that older age and comorbidities are significant prognostic factors for hospitalization and mortality [13-15,33,34]. Our study further provides evidence that older age, diabetes, and cardiovascular diseases as strong prognostic factors for the outcomes of COVID-19 patients.…”
Section: Discussionsupporting
confidence: 80%
“…We conducted whole-genome sequencing (WGS) of SARS-CoV-2 for all samples with PCR's Ct value of less than 30. As described in our previous studies [13,14,18,119], singlestranded cDNA was synthesized from total RNA extracted from the samples of COVID-19 patients by SuperScript™ III First-Strand Synthesis System (Thermo Fisher Scientific, MA, United States). Subsequently, the second strand was synthesized by COVID-19 ARTIC v3 primer pool design by SARS-CoV-2 ARTIC Network using Phusion™ High-Fidelity DNA Polymerase (Thermo Fisher Scientific, MA, United States).…”
Section: Whole-genome Sequencing Of Sars-cov-2mentioning
confidence: 99%
See 2 more Smart Citations
“…Under this system, a multitude of SARS-CoV-2 lineages and sub-lineages are identified and named accurately, including four variants of concern (VOCs: B.1.1.7, B.1.351, P.1 and B.1.617.2 corresponding to Alpha, Beta, Gamma and Delta labelled by WHO) and several variants of interest (VOIs) [12]. Since 2020, several teams and institutions (e. g., the Yogyakarta-Central Java COVID-19 Study Group and the West Java Health Laboratory) have conducted whole-genome sequencing (WGS) of SARS-CoV-2 strains circulating in various parts of Indonesia, and have shared genetic data and related metadata via the Global Initiative on Sharing Avian Influenza Data (GISAID) platform [13][14][15][16][17]. These efforts make it possible to gain insights into Indonesia's COVID-19 epidemic from a micro perspective.…”
Section: Introductionmentioning
confidence: 99%